2006
DOI: 10.1002/ajh.20682
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of chronic myeloid leukemia in eastern India

Abstract: Molecular breakpoint of the BCR-ABL fusion gene has been characterized for 122 chronic myeloid leukemia patients. Out of 122 cases, 33 b2a2, 69 b3a2, 2 e1a2, and 2 e19a2 cases have been detected. Six coexpressed both b2a2 and b3a2 transcripts. All the coexpressing samples had an A>G polymorphism at the putative splice branchpoint in intron 13. The T>C polymorphism in exon 13, reported to be linked to coexpression, was not present in all the coexpressing patients. No correlation of transcript type with platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 22 publications
0
29
1
Order By: Relevance
“…Co-expression of b2a2 and b3a2 transcripts has been linked to two polymorphisms, T to C at exon 13 and A to G at intron 13 (Meissner et al, 1998;Branford et al, 2002). However, in our study by Osman et al (2010) six PCR products from four patients were sequenced to confirm the products of four b2a2 and two b3a2 and one was found to harbor T to C at exon 13 and expressed only b2a2 transcript which might indicate that this exonic polymorphism is not obligatory for co-expression, as reported by Mondal et al (2006). Moreover, this polymorphism has no implication on the primary structure of BCR and BCR-ABL proteins.…”
Section: Gene and Chromosomal Rearrangementsmentioning
confidence: 50%
“…Co-expression of b2a2 and b3a2 transcripts has been linked to two polymorphisms, T to C at exon 13 and A to G at intron 13 (Meissner et al, 1998;Branford et al, 2002). However, in our study by Osman et al (2010) six PCR products from four patients were sequenced to confirm the products of four b2a2 and two b3a2 and one was found to harbor T to C at exon 13 and expressed only b2a2 transcript which might indicate that this exonic polymorphism is not obligatory for co-expression, as reported by Mondal et al (2006). Moreover, this polymorphism has no implication on the primary structure of BCR and BCR-ABL proteins.…”
Section: Gene and Chromosomal Rearrangementsmentioning
confidence: 50%
“…Co-expression of e13a2 and e14a2 transcripts has been reported in certain population groups: 13 per cent of Mexican, 2.5 per cent of Mexican Mestizos, 5.36 per cent of east Indian, 4.6 per cent of Sudanese and 4.38 per cent of north Indian population912131415. The occurrence of dual transcripts is not phase specific as it has been observed in all phases of the disease.…”
Section: Resultsmentioning
confidence: 97%
“…PCR primers were designed to amplify the breakpoint region ( BCR - ABL ) [breakpoint region forward (F) and reverse (R)], e13a2 and e14a2 transcript specific forward primers ( BCR exon 13 F and BCR exon 14 F) and a common ABL R primer, respectively to confirm the presence of dual transcript, ABL gene ( ABL control F and R), BCR gene ( BCR exon 10 F and 13 to check for polymorphisms in BCR region and BCR intron 13 F and BCR exon 14 R to check for the presence of intronic polymorphism) and the ABL kinase domain (First PCR-breakpoint region F and ABL exon 10 R followed by a second PCR using ABL kinase domain F and R primers). The list of primers used in the study is shown in Table I 57891011. Polymerase chain reaction (PCR) was performed using the Eppendorf Mastercycler gradient (Eppendorf Scientific, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Several reports have suggested that the type of the chimeric mRNA (e13a2 or e14a2) is associated with differences in the clinical and hematological characteristics of CML patients, despite that others failed to confirm any significant correlation (Kurzrock et al, 1988;Faderl et al, 1999b;De Lemos et al, 2005;Lucas et al, 2009;Sharma et al, 2010;Mondal et al, 2006a;Adler et al, 2009).…”
Section: Breakpoints Within M-bcrmentioning
confidence: 99%